The Influence of the Problem Based Learning Model Assisted by Powtoon Media on Science Learning Interest and Outcomes - St. Aminah, St. Aminah; Nurlina, Nurlina; Agustan S, Agustan S (Journal of Educational Sciences, 2025)
This study aims to determine the influence of the problem based learning model assisted by powtoon media on science learning interest and outcomes of fifth grade students in cluster I, Rumbia District. This quantitative study employed a quasi-experimental design. The design used was a quasi-nonequivalent control group design. The sampling technique used was random sampling. This design aimed to determine the effect between the experimental and control classes by administering a pretest and posttest. The population in this study were fifth-grade students in Cluster I, Rumbia District. Data collection techniques used questionnaires and tests. The data analysis techniques used were independent sample t-test and MANOVA which had previously tested the prerequisites for normality and homogeneity. Based on the results of the independent sample t-test, the sig. value was 0.000 <0.05, thus H0 was rejected and H1 was accepted. In the MANOVA test results, the sig. value was 0.000 <0.05, thus H0 was rejected and H1 was accepted, meaning that there was an influence of the problem-based model assisted by powtoon media on the interests and learning outcomes of fifth-grade students in science.